Rome wasn't burnt in a day : the real deal on how politicians, bureaucrats, and other Washington Barbarians are bankrupting America - Scarborough, Joe (New York, New York : HarperCollins Publishers, 2004)
The author charges both Republicans and Democrats with squandering tax dollars, discusses such experiences as his role in removing Newt Gingrich from office, and offers recommendations on how to address current political issues.
Keywords: United States Congresses -- Appropriations and expenditures; Political corruption -- United States; Budget deficits -- United States